Tasawuf Falsafi dan Refleksi Pendidikan Islam Membentuk Perilaku Ihsan - Hadarah, Hadarah (Tawshiyah: Jurnal Sosial Keagaman dan Pendidikan Islam, 2019)
The concept of a person's behavior (ihsan) about God develops among zuhud or ascetic experts (ascetic) as an embryo of Sufism. God is studied in depth through the approach of the heart and mind or pure logic (Taste and Ratio), so that their views of God are not limited to the opinions of the mutakallimin, but more than that. Their concept of the substance of God can be understood, is the source of all beauty (aesthetic) and the perfection of compounds and one, it is also believed that God is the source of absolute strength, power and iradat. God is the supreme creator, regulator of all events and the origin of all that exists (causa prima). The development of Sufism as a way and practice for realizing inner purity on the way to closeness to Allah SWT (takarrub Ila llah). Become a concern and attract the attention of Muslim thinkers with a background in theology and philosophy. From this group came a number of Sufi figures who were also philosophical, namely the Sufism dimension was rich in philosophical thoughts. These philosophical thoughts became an inspiration in the development of Islamic education methodology. Expected methodologies are methods that help facilitate understanding and lead to the perfection of God. Both through the human concept, human in its development, the concept of science and its function, the way humans obtain knowledge, as well as in the learning process and the functioning of the institution.